What is the Best Outsourcing Strategy? Nonlinear Association between the Outsourcing Degree of Institutional Care and the Costs of Substitute Care in Child Welfare within Finnish Municipalities. Issue 1 (1st January 2017) - Toikko, Timo
ABSTRACT: The main aim of the study was to explore the association of outsourcing degree to the cost of institutional care in child welfare. There was no essential difference in cost when the municipalities had outsourced either almost none or all of their services. The highest costs were associated with the situation wherein about half of services were outsourced. However, the association depended on the sizes of municipalities. Among the big municipalities the highest costs were associated with the situation wherein about a quarter of services were outsourced. Among the small municipalities the association was similar to the whole data.